The functions of a servant leader - Michiel Frederick Coetzer; Mark Bussin; Madelyn Geldenhuys (Administrative Sciences, 2017)
Servant leadership has been researched internationally and various types of favourable individual, team, and organisational outcomes have been linked to the construct. Different servant leadership measures have been validated to date and a clear distinction has been made between the theory of servant leadership and other leadership theories. However, it seems that research on the implementation of servant leadership within an organisation is still in need. The main functions of a servant leader are not yet conceptualised in the literature to help researchers or practitioners to implement servant leadership successfully within organisations. After conducting a systematic literature review, the main functions of a servant leader were identified. These functions were clustered into strategic servant leadership and operational servant leadership and supported by servant leadership characteristics and competencies as defined by current literature. The results of this study might help practitioners to develop servant leaders more effectively and assist organisations to cultivate a servant leadership culture within companies. Limitations and future research needs are discussed.
Keywords: 350; servant leadership; practice; organisational development; systematic literature review